2006
DOI: 10.1007/s10096-005-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of antifungal therapies in invasive fungal infections: review and meta-analysis

Abstract: Amphotericin B is the main therapeutic agent for the treatment of invasive fungal infections; however, it is associated with significant toxicities that limit its use. Other systemic antifungal agents have been developed to improve tolerability while maintaining the efficacy profile of conventional amphotericin B. Fifty-four studies involving 9,228 patients were assessed for the frequency of adverse effects of the main systemic antifungal agents. While the results suggest that liposomal amphotericin B is the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(40 citation statements)
references
References 65 publications
(47 reference statements)
1
36
0
1
Order By: Relevance
“…These reasons could explain the difference in the incidence of adverse effects in our study and previous reports. 29,30 The all-cause mortality in elderly patients with IFD is extremely high. In consistent with previous reports, 9 neutropenia, prolonged use of GC and immunosuppressants were significant in non-survivors with invasive mold infection.…”
Section: Discussionmentioning
confidence: 99%
“…These reasons could explain the difference in the incidence of adverse effects in our study and previous reports. 29,30 The all-cause mortality in elderly patients with IFD is extremely high. In consistent with previous reports, 9 neutropenia, prolonged use of GC and immunosuppressants were significant in non-survivors with invasive mold infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are various strategies relating to drug administration that can reduce the risk of adverse effects. These include sodium pre-infusion, routine premedication with an antihistamine and antipyretic, rationalizing concomitant nephrotoxic drugs and administration of c-amB as an extended or continuous infusion [6,[18][19][20]. The routine use of these strategies when administering c-amB is not included in any guideline and was not standard practice at our institution during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials and meta-analyses have reported no significant difference in the frequency of hypokalaemia between c-amB and l-amB [9,23,24]. However, there is substantial heterogeneity in the definition of hypokalaemia between studies [9,20]. Previously, studies have been limited by using end-of-treatment potassium as a marker of treatment-associated hypokalaemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations